The effect of patient experience with nurses and ward type on intention to recommend: Focusing on integrated nursing and caring service wards and general wards, 2020–2022 - Jinsun Kim; Seungju Kim (PLoS ONE, 2026)
Objective This study aimed to compared inpatients’ intention to recommend hospitals between integrated nursing and caring service wards (INCSW) and general wards (GW), and examined between patients’ experiences with nurses and recommendation intention. Methods This study analyzed 943 inpatients (INCSW = 223, GW = 720) using the Korea Medical Service Experience Survey (2020–2022). Intention to recommend and nurse experience were measured on 5-point Likert scales and treated as approximately continuous, a common approach that supports the use of multivariable linear regression. Ward differences were assessed using t-tests, and effect sizes were summarized using Cohen’s d. Results Patients in INCSW reported higher recommendation intention than those in GW (Mean 4.11 vs 3.98), with a small effect size (Cohen’s d = 0.27). However, ward type was not independently associated with recommendation intention in the fully adjusted model. All nurse experience domains were positively associated with recommendation intention, with courtesy showing the largest coefficient ( β = 0.27, 95% CI 0.17–0.37). Conclusion Although recommendation intention was slightly higher among INCSW patients in unadjusted comparisons, ward type was not independently associated with willingness to recommend after adjustment. In contrast, all nurse experience domains were positively and significantly associated with patients’ willingness to recommend the hospital. Strengthening nurse communication competencies, supported by ward-level monitoring and feedback-based training, may enhance patient experience and willingness to recommend.